"I feel too lethargic to do physical activity": Perceptions of Iranian adults on the barriers to perform regular physical activity - Behrouz Fathi; Haidar Nadrian; Mina Hashemiparast; Saeed Nikookheslat; Safooreh Esmaeilzadeh; Rahim Khodayari-Zarnaq (Tabriz University of Medical Sciences, 2021)
Background: Despite the intention to perform physical activity (PA), a number of individuals cannot manage to have PA program on a regular basis. In this study we explored the barriers of regular PA behavior among healthy adults in Tabriz, Iran. Methods: This qualitative study with a conventional content analysis approach, was carried out from June to September 2020. Nineteen 30-59 years old individuals, were purposefully (purposive sampling) selected to participate in the study. The participants were formerly registered as "physically inactive" in the health records of Tabriz Health System. Individual semi-structured interviews were conducted until data saturation. Data were managed using MAXQDA-10 software. Results: The barriers of regular PA that emerged from our data were being listless and lethargic, non-supportive environment, disintegration in PA education chain, and restrictive social norms. Conclusion: Our findings uncover several PA barriers that are less discussed in the literature. Poor level of regular PA among adults in Iran, as a developing context, is rooted in perceptions with social and economic origins, which should be taken into account by public health policy makers while planning PA promotion programs in such communities. To promote regular PA among healthy adults in developing countries, regular PA programs should be tailored to bridge the gap between their recognition of PA barriers and subsequent behavior change through creating group dynamics highlighting the measures to diminish the behavior.